Collective Memory of Java's North Coast Road (Pantura) in Central Java in the New Order Period: A Historical Study - Endah Sri Hartatik (Forum Ilmu Sosial, 2023)
Jalan Raya Pantai Utara (commonly referred to as Pantura) has given rise to a multitude of phenomena that have since embedded themselves as shared memories among the communities residing along its route, as well as those who have journeyed along this roadway. These collective recollections encompass a range of elements, including the historical Jalan Raya Pos, notorious for the harsh policies enacted during Daendels' era, instances of criminal activities, traffic accidents, the presence of prostitution, vibrant graffiti art, the distinctive strains of Pantura's Dangdut music, and various others. However, this reservoir of collective memory is gradually dissipating, largely due to the Pantura highway making way for the Trans Java Toll Road. The distinctive phenomena and symbols that once adorned the landscape of Jalan Pantura have the potential to be pieced together into a comprehensive narrative within the annals of collective history. Employing historical methodologies and conducting oral history interviews served as the foundation for sourcing information in this study. Through meticulous exploration of archival records and engaging in dialogues with carefully selected informants, this research underscores that the intricate web of recollections surrounding the complexities of Pantura's history was shaped incrementally, parallel to the evolution of its economic, social, political, and cultural facets. The findings of this research underscore that the collective memory encapsulating the multifaceted essence of Pantura's past has been an evolving creation intertwined with the progression of economic, social, political, and cultural dimensions. Significantly, we continue to encounter traces of this collective memory in a myriad of artistic expressions, melodious songs, and numerous other manifestations that persist even today.